PENGEMBANGAN SITUS WEB UNTUK PENYEBARAN DAKWAH ORGANISASI PEMUDA PERSATUAN ISLAM BANJARAN - Wulan, Sri Ratna; Firdaus, Lukmannul Hakim; Maspupah, Asri; Fauzi, Cholid; Wirasta, Wendi; Min, Joe Lian (Jurnal Abdi Insani, 2024)
Pemuda Persis, as a part of the Islamic Union, faces the challenge of a demographic in spreading their dakwah. The main issue is the dynamics of member development and participation influenced by demographic, geographic, social, and psychological changes. The current priority for the management is to focus on comprehensive development to create quality cadres. They have created preaching content on YouTube and Instagram but have not effectively reached all members, as seen from the viewership on each platform. The goal of this Community Service Program (PkM) is to develop an Islamic study website as a platform for study and preaching content for Pemuda Persis Banjaran members and the general public. The PkM consists of seven stages: 1) Software needs analysis; 2) Software design; 3) Software development implementation; 4) Installation and testing of the software; 5) Socialization and training; 6) Assistance and evaluation; 7) Software launch. The result of this PkM is a website with a Content Management System (CMS) and a portal to display the dakwah content such as study programs, articles, and news. Three types of users are identified: admin, registered website members, and non-members. Admin can manage articles, new pages, menus, study programs, and study program categories. Additionally, Admin can also view dakwah content frequently accessed by members. Meanwhile, members can manage profiles and view specific member articles. Non-members can only view articles, study programs, and news. The level of user satisfaction with the application is measured using the System Usability Scale (SUS) survey.  The SUS score of 79.3 indicating that the generated website is effective, efficient, and satisfactory. Therefore, it can be concluded that this PkM has significantly contributed well to solving the partner's problem.